2019
DOI: 10.1055/s-0039-1691839
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Support during Bronchiolitis Due to One Virus versus More Than One Virus: An Observational Study

Abstract: Bronchiolitis is common during infancy and frequently leads to pediatric intensive care unit (PICU) admission. This study aimed to determine if there is a difference in the duration of respiratory support when bronchiolitis is due to one virus or more than one virus. This is a retrospective, observational study of cases admitted to PICU with confirmed bronchiolitis. There were 306 cases analyzed, 70% (215/306) were infected by a single virus and 30% (91/306) were infected with more than one virus. Both groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
3
1
0
Order By: Relevance
“…Coleman et al observed a similar duration of respiratory support and PICU hospitalization in patients infected with a single virus compared with patients infected with more than one virus. 19 These data are consistent with the results published by Ghazaly and Nadel that did not find out clinical or radiologic differences between single and multiple VRIs in a cohort of 422 children. 13 Other studies show, however, conflicting data; in particular, recently, the multivariable regression analysis of a study on 477 infants admitted to the PICU with one or multiple organisms showed an association between coinfections and higher odds of longer PICU stay, prolonged mechanical ventilation, central line requirement, and bacterial coinfection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Coleman et al observed a similar duration of respiratory support and PICU hospitalization in patients infected with a single virus compared with patients infected with more than one virus. 19 These data are consistent with the results published by Ghazaly and Nadel that did not find out clinical or radiologic differences between single and multiple VRIs in a cohort of 422 children. 13 Other studies show, however, conflicting data; in particular, recently, the multivariable regression analysis of a study on 477 infants admitted to the PICU with one or multiple organisms showed an association between coinfections and higher odds of longer PICU stay, prolonged mechanical ventilation, central line requirement, and bacterial coinfection.…”
Section: Discussionsupporting
confidence: 92%
“…Rates of viral coinfection reported in other studies range from 6% to more than 30%, but the correlation with greater disease severity and longer length of ICU staying is unclear to date. Coleman et al observed a similar duration of respiratory support and PICU hospitalization in patients infected with a single virus compared with patients infected with more than one virus 19 . These data are consistent with the results published by Ghazaly and Nadel that did not find out clinical or radiologic differences between single and multiple VRIs in a cohort of 422 children 13 .…”
Section: Discussionsupporting
confidence: 82%
“…In most studies RSV-positive infants had a prolonged PICU length of stay, whereas we did not nd any correlation in our study [7,16,18]. Infants with viral coinfection did not have a longer PICU length of stay, which is consistent with most studies, but they did require more invasive ventilation [19,23,24]. As in other studies, we found that the presence of apneas was a risk factor for prolonged PICU length of stay, however, to our knowledge no publication showed that the presence of bradycardia further increased the PICU length of stay [7,8,21].…”
Section: Discussionsupporting
confidence: 86%
“…They also did not find an association between disease severity and co-infections, which was corroborated by a recently published meta-analysis [39]. A retrospective observational study on mechanically ventilated children with bronchiolitis admitted to the PICU showed no differences on duration of respiratory support or PICU length of stay between bronchiolitis caused by only one virus and more than one virus [40]. Hospital length of stay, however, was longer in the co-detection group.…”
Section: Discussionmentioning
confidence: 72%